Analysis of the Efficiency of Hospital X Services Based on Electronic Medical Records: Systematic Literature Review, PRISMA, and Vosviewer - Kosasih Kosasih; Desi Septiani; Widya Anggraini; Fitri Handayani; Ali Yusran Afrizal; Vip Paramarta (Advances in Human Resource Management Research, 2026)
Purpose: This study aims to analyze the efficiency of hospital services based on the implementation of Electronic Medical Records (EMR), particularly in improving operational performance and service quality within healthcare organizations. Research Method: The study employs a Systematic Literature Review (SLR) based on the PRISMA approach, combined with bibliometric analysis using VOSviewer. A total of 37 relevant articles published between 2020 and 2025 were systematically selected and analyzed to identify research trends and conceptual relationships. Results and Discussion: The findings indicate that EMR implementation significantly improves hospital service efficiency by reducing operational costs, enhancing clinical decision-making, and optimizing service processes. Bibliometric analysis reveals a shift in research trends toward digital integration, system interoperability, and the development of smart hospital systems, highlighting the growing importance of technology-driven healthcare management.   Implications: The study implies that achieving optimal efficiency through EMR requires strong organizational readiness, effective system integration, and continuous innovation. Policymakers and hospital management must adopt a holistic and data-driven approach to ensure sustainable improvements in healthcare service efficiency.